Clinical and epidemiological characterization of infection associated with ischemic stroke in patients over 60 years of age - Alexis Suárez Quesada; Alexis Álvarez Aliaga; Andrés José Quesada Vázquez; Ezequiel Ernesto López Espinosa; Liannys Lidia Naranjo Flores (Medisur)
Foundation: Stroke is the third cause of death worldwide. Infection is the most important medical complication due to its impact on morbidity and tripling the number of deaths. Objective: to characterize from a clinical and epidemiological point of view the infection associated with ischemic stroke in patients over 60 years of age. Methods: A descriptive case series study was conducted, which included patients diagnosed with ischemic stroke treated at the Carlos Manuel de Céspedes Hospital, in the Bayamo municipality, Granma province, from January 1, 2018 to December 31, 2022. Results: Of a total of 490 patients, 75 (15.3%) developed infection associated with ischemic stroke. When comparing both groups of patients, a significant difference was found regarding the history of heart failure, atrial fibrillation, and presence of neurogenic dysphagia. Patients who developed this complication were older, had a poorer level of consciousness, greater stroke severity, and nutritional risk. Respiratory infection predominated, with 7.8%; and enterobacteria (29.3%) was the most observed microorganism. Conclusions: The main clinical, epidemiological and microbiological characteristics were observed, among which the most notable were age over 70 years, stroke severity, history of heart disease, and nutritional risk at the time of the onset of the ischemic event.